การศึกษาเปรียบเทียบอัตราผลตอบแทนของประกันชีวิตแบบบำนาญ - วรานิษฐ์ วีระปิติพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The objective of this project is to compare the internal rates of return of two annuity life insurance plans. Setting a desired retirement pension, we determine the age at which the annuity life insurance should commence as well as the insurance premiums that will yield the highest internal rate of return. The insurance plans to be compared are Annuity - Fix plan of AIA Life Insurance Company and Muang Thai 8560 plan of Muang Thai Life Assurance Company. The result shows that, no matter when the annuity life insurance is commenced, Annuity - Fix plan will provide higher internal rate of return than Muang Thai 8560 plan when the insured’s death happens from 61 to 73 years old. In that case, the life coverage is the present value of guaranteed annuity. And in case that the insured’s death happens from 74 years old to the end of the policy contract, Muang Thai 8560 plan will provide higher internal rate of return than Annuity - Fix plan.